Tradisi Lisan sebagai Media Evaluasi Eksistensi Bahasa Daerah - Lilik Rita Lindayani (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
The oral tradition is a form of interpretation of past experiences and future investment of a great nation that is one of the main media is the local language. Local languages present in every activity of oral tradition and even the meaning of spoken words sometimes cannot be matched or automatically translated into Indonesian. This phenomenon is thus interest to be presented. Wherein, inter oral traditions and local languages are both very exocentric, which is fused but do not have the central element. In other words, the local language to be powerful when embedded in tradition, and vice versa. The paper raised the question about the existence of oral tradition as an evaluation of the existence of vernacular media aimed at exposing the functions and role of oral tradition as a medium for evaluation. The originality of local language is qualitatively exposed to any activity of their ethnic traditions, both in the form of traditional narrative and oral literature. Thus, it can be concluded that through the existence of oral tradition, can be seen the existance of “local language” in the community of speakers in the area said that regional language, the language is still alive deemed to exist, dim, or have disappeared altogether. Keywords: oral tradition, evaluation, regional language.